Participatory multicriteria assessment of maize cropping systems in the context of family farmers in the Brazilian Cerrado. Issue 5 (2nd September 2020) - Xavier, José Humberto Valadares; Gomes, Mário Conill; Anjos, Flávio Sacco dos; Scopel, Eric; Silva, Fernando Antônio Macena da; Corbeels, Marc
ABSTRACT: Conservation agriculture (CA) is recognized as a promising crop management strategy for sustainable agricultural intensification. The objective of this study was to evaluate CA cropping systems for rainfed maize as an alternative to the traditional tillage-based cropping systems (CT) in the context of family farms, using a multi-criteria model that represents the point of view of farmers. Farmers considered several aspects for evaluating the cropping systems, thatwere systematized in the model through five criteria (with sub-criteria): (a) costs; (b) yield; (c) labour; (d) human health and environment; and (e) production risks. CA did not differ from CT for the 'costs' criterion but was superior for the 'yield' and 'labour' criteria. In contrast, CT obtained better ratings for the criteria 'human health and environment' and 'production risks'. Considering all criteria, CA was better appraised than CT. However, a new local policy measure that subsidizes the hiring of mechanized tillage services overturns this outcome, indicating the importance of exogenous factors. Overall, the participatory processes in building the model allowed us to better understand the reasons of adoption or non-adoption of CA by small-scale farmers in the tropics.